2015
DOI: 10.1108/tc-02-2014-0004
|View full text |Cite
|
Sign up to set email alerts
|

Core characteristics, treatment process and retention in therapeutic communities for addictions: a summary of four studies

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Since these individuals share a similar profile to those who are most likely to leave residential treatment services prematurely (Darke, Campbell & Popple, 2012;Goethals et al, 2015;Joe, Simpson & Broome, 1998;Keen et al, 2001;Meier, 2005;NICE, 2007;National Treatment Agency, 2012;Ravndal & Vaglum, 1994), it would seem that the WH initiative was appropriately catering for those least likely to complete treatment and therefore most in need of support.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since these individuals share a similar profile to those who are most likely to leave residential treatment services prematurely (Darke, Campbell & Popple, 2012;Goethals et al, 2015;Joe, Simpson & Broome, 1998;Keen et al, 2001;Meier, 2005;NICE, 2007;National Treatment Agency, 2012;Ravndal & Vaglum, 1994), it would seem that the WH initiative was appropriately catering for those least likely to complete treatment and therefore most in need of support.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal evidence suggests that WHs have led to longer residential treatment stays and higher treatment completion rates (Vandevelde, 2014). However, there has been no empirical research exploring 'how' WHs might have achieved this (Goethals et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a later study of a new innovation in residential treatment, Tompkins et al . [41] explored how welcome houses [42], which provide a relatively gentle introduction to the structured, rule‐bound approach of therapeutic communities, affected treatment retention. The differentiating process, when applied to their descriptive analyses, suggested that welcome houses increased retention amongst people who had never been in residential treatment previously or who had complex needs.…”
Section: Conceptualisingmentioning
confidence: 99%